Challenges faced by learners and teachers in special classes in secondary schools: the case of Dzivaresekwa District in Harare. - Mangwaya, Ezron (World Academy of Science, Engineering and Technology (WASET), 2016)
Education systems, the world over have tended to treat disabled learners differently from the able bodied. This has been done with the express intention of providing learners with disabilities with conditions which take into account their special conditions. Since the Salamanca report education ministries have tended to gravitate towards inclusion and or the establishment of special classes in regular schools. In Zimbabwe the focus was on the establishment of special classes in regular schools. This study explores challenges which teachers and learners have experienced in such a set up with a view to suggesting interventions that can be adopted by the Ministry of education and more specifically by teachers who operate in special education classes.